Neuroprotective effect against cerebral ischemia of passiflora foetida - Wattanathorn J. (2017)
Problem statement: Although cerebral ischemia induced by stroke has been regarded as the important problem worldwide, the therapeutic efficacy is still inadequate. Since the free radicals are implicated in the pathophysiology of cerebral ischemia, the prophylactic protection against stroke with neuroprotective agent possessing antioxidant effect has gained much attention. Therefore, this study was designed to determine whether the alcoholic extract of Passiflora foeida, a plant possessing antioxidant activity, could protect against brain damage and impairment in the cerebral ischemia induced by the occlusion of Middle Cerebral Artery Occlusion (MCAO). Approach: Male Wistar rats, weighing 300-350 g, were orally given the extract once daily at doses of 25, 100 and 400 mg kg -1 BW at a period of 2 weeks before and 3 weeks after the occlusion of right Middle Cerebral Artery (MCAO). The animals were assessed the cerebral infarction volume at 24 h after occlusion while the neurological score and % of foot withdrawal reflex in respond to mechanical stimuli were performed after single dose and every 7 days throughout the experimental period. Results: Rats subjected to P.foetida at dose of 25 mg kg -1 BW significantly decreased brain infarct volume both in cortical and sub cortical structures. The increasing doses further to 100 and 400 mg kg -1 BW could produce the significant reduction only in cerebral cortex. In addition, it was found that the plant extract could enhance neurological score and improved sensory response to both mechanical and temperature stimuli. Conclusion: The current study clearly demonstrates the neuroprotective effect of P.foetida. Therefore P.foetida may provide the advantage as functional food to protect against cerebral ischemia induced by stroke. However, further researches about possible active ingredient and the precise underlying mechanism are still necessary. © 2012 Science Publications.